The Influence of Celebrity Endorsements and Brand Image on TikTok Users' Purchase Intentions (Case Study of State Administration Science Study Program Students, Makassar State University) - Andi Asmarani Syaputri; Muhammad Rivai; Muhammad Luthfi Siraj (Universitas Negeri Makassar, 2026)
Objective from study This is For evaluate in a way comprehensive And objective How environment selective And causal influence intention purchase user TikTok . Study This use method analysis descriptive quantitative . For reach objective the researcher use method data collection in the form of questionnaires , observations , and documentation , with amount sample nine tens two respondents . Analysis done with using SPSS Statistics Version 23 which includes test validity And reliability , test assumptions classic , analysis multiple linear regression , t test , f test , and coefficient determination . Findings show that indicator For each support variable celebrity (X1), image brand (X2), and intention buy (Y) is in range Good until very Good . This matter show that Good image brand (X2) or support celebrity (X1) is influential significant to variable intention buy (Y).